A Register‐Based Study of Diseases With an Autosomal Recessive Origin in Small Children in Denmark According to Maternal Country of Origin. Issue 4 (13th May 2015) - Gundlund, Anna; Hansen, Anne Vinkel; Pedersen, Grete Skøtt; Villadsen, Sarah Fredsted; Mortensen, Laust Hvas; Brøndum‐Nielsen, Karen; Andersen, Anne‐Marie Nybo
Abstract Background Compared with children born of Danish mothers, the mortality of children, born and living in Denmark, is significantly increased in those with a mother from Afghanistan, Iraq, Pakistan, Somalia, and Turkey. Consanguinity has been suggested to account for part of this disparity. Since information on consanguinity is lacking, this suggestion is difficult to test. With an indirect approach, we addressed this question by comparing the risk of diseases with autosomal recessive inheritance in children born in Denmark of Danish‐born women and of women born in these five countries, respectively. Methods All children born in Denmark (1994–2010) were followed until 5 years of age or end‐of‐study period for the risk of hospitalisation with diseases of autosomal recessive aetiology, and therefore considered consanguinity‐related. Diagnoses of autosomal recessive diseases were identified using two different methods: a literature review of consanguinity‐associated diseases and a search in the Online Catalogue of Human Genes and Genetic Disorders. Risks were also calculated for diseases with known non‐autosomal recessive aetiology (considered non‐consanguinity‐related). We estimated adjusted hazard ratios for the diseases in children of foreign‐born women compared with children of Danish‐born women. Results Compared with offspring of Danish‐born women, the risk of a consanguinity‐related disease was significantly increased in children of foreign‐born women, although the absolute risk was low. The risk of non‐consanguinity‐related diseases did not differ between the groups compared. Conclusions The findings support the hypothesis that consanguinity accounts for some, however a minor part, of the disparity in child mortality among migrants in Denmark.